AI-driven analytics : how artificial intelligence is creating a new era of analytics for everyone - Zinsmeister, Sean; Yeung, Andrew; Garrett, Ryan (O'Reilly Media, 2019)
What happens when you incorporate artificial intelligence into your analytics portfolio? A decade ago, business intelligence applications were simply trying to become more visual. Now, analytics software provides intuitive search and AI-driven features as an integral part of the experience. This practical ebook explains how business professionals like you can AI to find insights buried in your corporate data to make the right decision. Sean Zinsmeister, Andrew Yeung, and Ryan Garrett take you through the many benefits of AI-driven analytics for the enterprise. Analysts will be able to reduce analysis from days to minutes. Decision makers, whether they're in the boardroom or on the frontlines, will find insights faster and deeper than is possible with static BI dashboards. This ebook explains how AI can increase data literacy by helping business people discover what to look for in the first place. Delve into the origins of AI and BI and see how the two evolved simultaneously Learn why AI requires database and analytics technologies that operate at massive volume and speed Understand common AI algorithms and applications used in analytics Explore the variety of technology choices for implementing AI Learn how nontechnical users can leverage AI to conduct analyses Examine AI-driven analytics in retail, financial services, manufacturing, and high tech.